2018
DOI: 10.1039/c7ta09264d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and facile synthesis of hierarchically mesoporous TiO2–B with enhanced reversible capacity and rate capability

Abstract: A rapid and facile synthetic route has been developed to fabricate hierarchically mesoporous TiO2–B, which is composed of nanoparticles and exhibits enhanced reversible capacity and rate capability in lithium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…When compared with previous literature, the specific capacity of the optimal material (TIO220_12) was higher than Li 4 Ti 5 O 12 and other TiO 2 materials, as well as other carbonaceous materials. ,,, However, we found that TIO220_12 was able to maintain excellent stability and possessed a long life cycle compared to carbonaceous materials and titanium oxide-based materials. Moreover, the precursors used to prepare TiO 2 (B) nanorods were naturally abundant, nontoxic, environmentally friendly, and low cost.…”
Section: Electrochemical Measurementmentioning
confidence: 46%
“…When compared with previous literature, the specific capacity of the optimal material (TIO220_12) was higher than Li 4 Ti 5 O 12 and other TiO 2 materials, as well as other carbonaceous materials. ,,, However, we found that TIO220_12 was able to maintain excellent stability and possessed a long life cycle compared to carbonaceous materials and titanium oxide-based materials. Moreover, the precursors used to prepare TiO 2 (B) nanorods were naturally abundant, nontoxic, environmentally friendly, and low cost.…”
Section: Electrochemical Measurementmentioning
confidence: 46%
“…25 The peaks of TO ev are basically tallies with the Raman modes of the TiO 2 (B) phase based on previous studies (Figure S4b). 26 The stoichiometry and chemical state were studied by X-ray photoelectron spectroscopy (XPS). In Figure 2c, the survey spectra show the existence of O, Ti, and K and nonexplicit metal oxides in KTO samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthesis of TiO 2 (B) by a Two-Step Hydrothermal Reaction: TiO 2 (B) was typically synthesized by the method in Note S1 (Supporting Information) and denoted as TiO 2 @GA-TBOT. [28] The synthetic approaches of TiO 2 (B) were further optimized by i) adding more GA (named as TiO2@4.5GA-TBOT, TiO2@5.5GA-TBOT), and ii) changing the addition order of GA and tetrabutyl titanate (TBOT, added before GA). Specifically, the TBOT was dissociated into butanol (Bu) in the absence of GA, which was evaporated with water during stirring (the evaporated water was replenished and the GA was then added) and the as-prepared sample was named as TiO 2 @TBOT-GA.…”
Section: Methodsmentioning
confidence: 99%